PENGUJIAN KESUKSESAN IMPLEMENTASI ERP (ENTERPRISE RESOURCE PLANNING) MENGGUNAKAN MODEL DELONE DAN McLEAN PADA PT SARI HUSADA GENERASI MAHARDHIKA - Siti Rahmi (ABIS: Accounting and Business Information Systems Journal, 2013)
This study aims to testing and obtain empirical evidence implementation of Enterprise Resource Planning (ERP)PT Sari Husada Generasi Mahardhika Yogyakarta using the updated DeLone and McLean model. Delone and McLean model is a model of successful testing of information technology system that are based on processes and causal relationshipof the dimensions of the model. The dimensions of this model are quality system, information quality, system usage, user satisfaction and net benefits.The research method is quantitative method of mail survey methods to company officials who daily use the ERP. This study uses version 2.0 SmartPLS program assitence as a tool to test hypotheses in the study.Based on the results of data analysis, in getting that all constructs in this study has fulfilled the requirements of validity and reliability. Where to terms of validity, the value of loading factor must exceed 0,7 and its reliability requirement given the level of Cronbach’s Alpha above 0,7. Based on the results of hypothesis testing shows there are several hypothesis are supported, such as HI,HI2,H3,H5,H6,H8. And there are also the hypothesis that are not supported, for example H4,H7,H9.